Seeking the -ational in derivational morphology. Issue 11 (1st November 2016) - Libben, Gary; Jarema, Gonia; Derwing, Bruce; Riccardi, Alessandra; Perlak, Danuta
ABSTRACT: Background : Derived words have constituted an important bridge between aphasiology and psycholinguistics by addressing the extent to which morphology affects representation and processing in the mind/brain. Aims : Our goal was to assess how properties of whole words and their overlapping substrings affect the manner in which English derivationally suffixed words are recognised and produced. Methods & Procedures : We probed the processing of multimorphemic words containing strings of two derivational suffixes by healthy adult participants, employing both a progressive demasking naming task and a typing task. The progressive demasking paradigm that we employed integrates word recognition and production by requiring that a participant recognises a progressively demasked stimulus and then say it as quickly as possible. The typing task allowed us to focus on segment by segment aspects of processing during production by enabling us to construct per-letter typing times for each region of a word. Outcomes & Results : We found converging influences across the tasks that correspond to the properties of roots, stems, suffixes and suffix strings. Conclusions : We interpret these effects to accord with a perspective that emphasises the dynamic nature of the lexical processing system and massive interconnectivity within it. This has implications for unimpaired processing and for the word processing challenges experienced by people with aphasia.